The Contribution of Sangga Buana Community as a Learning Media of Civic Engagement Education Based on Ecological and Cultural - Digdoyo, Eko; AR, Endang Danial; Bestari, Prayoga; Gunawan, Rudy (Graduate Program Magister Manajemen Pendidikan, 2021)
The aim of this article was developing learning material for Civic Engagement Education based on ecological and cultural wisdom. The object of the study was the Central Sangga Buana Karang farmer community. The theoretical approaches that are considered relevant are those that are anthropological, ecological, and biological in nature. The results of the study show that Jakarta, apart from being the center of the economy, politics-bureaucracy, education and culture, as well as the center for the development of science and technology, is generally also the center of urbanization from various motives and backgrounds (migration). As a result of migration and population development that is not in line with geographical conditions, environmental and demographic management are to be separate problems that cannot be resolved by DKI Jakarta Government. For instance, the rampant illegal settlements have caused damage and pollution to the environment. However, in the South Jakarta area, especially in the Pesanggrahan Karang Tengah River watershed, there was a protected urban forest area that has been successfully managed by Sangga Buana volunteers using an ecological and cultural wisdom approach. This community efforts can be developed as one of the study materials for Community Citizenship Education.Â Keyword: Sangga Buana Community, Civic Education, Ecology Wisdom